Optimization of extrudate swell during extrusion-based additive manufacturing process - Cherouat Abel; Barriere Thierry; Wang Hong (E3S Web of Conferences)
Die swell is the expansion of the extrudate diameter upon exiting the die, resulting from the polymer melt or ink undergoes high shear stress due to the pressure-driven flow, viscoelastic relaxation phenomenon and the molecular chains stretching and oriented in the flow direction. Die swell affects dimensional accuracy and interlayer bonding and it's crucial to understood and controlled for high-precision manufacturing. It can be affected by multiple factors including material properties and processing parameters that can be coupled and it is difficult to fully understand their effects. To minimize or control extrudate swell it is necessary to identify the optimal combination of process parameters using Orthogonal Arrays. In this study, Orthogonal Experimental Design is used to optimize extrudate swell during extrusion-based additive manufacturing MEX of biodegradable polylactic acid material. It allows to systematically investigate the influence of multiple process parameters and their interactions on the swell ratio, using a minimal number of experiments. Simulating swell during extrusion with COMSOL Multiphysics requires combining computational fluid dynamics and Level Set method with rheological modeling of the extruded material. The results and analyses of the numerical simulation were used to predict and optimize the extrudate swelling in the MEX process.